Promosi Batik Inklusif Karya Siswa Sekolah Luar Biasa (SLB) Desa Reksosari melalui Media Sosial - Agus Mukholid; Alexander Gibson Xaverius Sihotang; Anisa Meliana Tri Pasha; Disti Nurul Khoiriyah; Dwi Wulandari; Elida Rifghana Nur; Fanny Anggraini; Muhammad Fathan Anandita; Novyta Puspasari; Rifda Nahya Bilqiis Adzanisya; Yuliana Ismi (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Batik is an Indonesian cultural heritage recognized by UNESCO, rich in artistic, philosophical, and social values. Beyond its cultural significance, batik can serve as a tool for education and empowerment, including for students with special needs. One technique, batik ciprat, is particularly suitable because it is simple, flexible, and easy to adapt, making it an effective medium for inclusive learning. The Community Service Program (KKN) UNS 273, conducted from July to August 2025 at SLB NU Reksosari, Semarang Regency, aimed to enhance students’ vocational skills through batik ciprat training. In addition, the program promoted students’ works through social media as a strategy to support social inclusion and creative economic development. A participatory approach was applied throughout the program, covering preparation, implementation of training, and promotion of students’ creations. The results showed positive responses from the surrounding community, increased students’ self-confidence, and potential collaboration with local SMEs. The program not only preserves the batik culture but also empowers SLB students, opens economic opportunities, and strengthens their participation in social activities. Recommendations for future development include optimizing social media usage, collaborating with local communities, strengthening product branding, integrating e-commerce platforms, and conducting offline activities to enhance promotion and direct engagement with the public.